Keabsahan Penguasaan Tanah Timbul Perspektif Hukum Pertanahan Indonesia - Oktavia , Vanessia; Herning Sitabuana, Tundjung (LPPM Universitas Ekasakti Padang, 2023)
Land reclamation has become a significant issue in Agrarian Law, mainly due to its utilization by the local community, which constitutes an error and leads to the unclear ownership and control of reclaimed land. This is because reclaimed land is directly controlled by the state. The purpose of this research is to examine the Validity of Reclaimed Land Ownership from the Perspective of Indonesian Land Law. The research method employed is a juridical-normative approach with a descriptive research specification. The data types include secondary data, and the data sources consist of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique utilized is literature review, and the data analysis technique is qualitative. Essentially, ownership and control rights over reclaimed land are rights held by the state. For individuals or communities seeking to control reclaimed land, obtaining prior permission from the government is required, typically by submitting a land rights application to the Land Office with jurisdiction over the location of the land in question.